Double progressivity of infrastructure financing through carbon pricing — Insights from Nigeria. (2022) - Dorband, Ira Irina; Jakob, Michael; Steckel, Jan Christoph; Ward, Hauke
Highlights: The consumption incidence of a carbon tax and fossil fuel subsidy reform would reduce inequality in Nigeria. Revenue recycling toward basic infrastructure access (electricity, water, sanitation, telecommunication) would also be progressive. The overall less affluent, rural households would benefit more, given lower infrastructure access levels and lower-carbon consumption. The consumption incidence varies more within (horizontally) than across (vertically) rural and urban income groups. Abstract: Carbon taxes and fossil fuel subsidy reforms have been recognized as an efficient means to mobilize substantive domestic resources for sustainable development. Yet, despite their advantages compared to other taxes, concerns about potential adverse impacts on poverty and inequality have discouraged many countries from such fiscal reforms. This paper estimates which absolute and relative equity effects a comprehensive carbon pricing reform would have on households within and between income groups in Nigeria. We further analyze the distributional effects of revenues being recycled into basic infrastructure development and social safety nets. We assess the expected consumption effects of six policy packages across rural and urban income groups, combining environmental-extended input-output data with detailed household survey data. Our results suggest that, relative to their income, lower-income households would bear a smaller consumption burden from carbon pricing than high-income households, while enjoying greater gains from uniform cash transfers or access to improved water, sanitation, electricity, or telecommunication infrastructure. Additionally, if spent efficiently, such investments could disproportionally benefit the overall poorer rural population due to larger initial access gaps.